The Development of Coping Stress, Neurophysiology, Social Relationships, and Resilience During Childhood and Adolescence - Skinner, Ellen A.; Zimmer-Gembeck, Melanie J; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This book traces the development of coping from birth to emerging adulthood by building a conceptual and empirical bridge between coping and the development of regulation and resilience. It offers a comprehensive overview of the challenges facing the developmental study of coping, including the history of the concept, critiques of current coping theories and research, and reviews of age differences and changes in coping during childhood and adolescence. It integrates multiple strands of cutting-edge theory and research, including work on the development of stress neurophysiology, attachment, emotion regulation, and executive functions. In addition, chapters track how coping develops, starting from birth and following its progress across multiple qualitative shifts during childhood and adolescence. The book identifies factors that shape the development of coping, focusing on the effects of underlying neurobiological changes, social relationships, and stressful experiences. Qualitative shifts are emphasized and explanatory factors highlight multiple entry points for the diagnosis of problems and implementation of remedial and preventive interventions. Topics featured in this text include: Developmental conceptualizations of coping, such as action regulation under stress. Neurophysiological developments that underlie age-related shifts in coping. How coping is shaped by early adversity, temperament, and attachment. How parenting and family factors affect the development of coping. The role of coping in the development of psychopathology and resilience. The Development of Coping is a must-have resource for researchers, professors, and graduate students as well as clinicians and related professionals in developmental, clinical child, and school psychology, public health, counseling, personality and social psychology, and neurophysiological psychology as well as prevention and intervention science.
Section I: Constructing "Developmentally-Friendly" Conceptualizations of Coping -- Chapter 1. Coping as Action Regulation Under Stress -- Chapter 2. Ways and Families of Coping as Adaptive Processes -- Section II: Review of Research on the Development of Stress Reactivity and Ways of Coping -- Chapter 3.Age Differences and Changes in Ways of Coping Across Childhood & Adolescence -- Chapter 4. Neurophysiological Developments that Underlie Age-Related Changes in Coping -- Section III: Normative Development of Coping within the Context of Relationships with Caregivers -- Chapter 5. Development of Coping in Newborns -- Chapter 6. Development of Coping During Infancy -- Chapter 7. Development of Coping During Toddlerhood -- Chapter 8. Development of Coping During Early Childhood -- Chapter 9. Development of Coping During Middle Childhood -- Chapter 10. Development of Coping During Adolescence -- Section IV: Foundations of Coping and its Differential Development -- Chapter 11. Early Adversity, Temperment, Attachment, and the Differential Development of Coping -- Chapter 12. Parenting, Family Stress, Developmental Cascades, and the Differential Development of Coping -- Chapter 13. Conclusion. .
Keywords: Developmental psychology; Child and School Psychology